Association of Early Postinduction Adalimumab Exposure With Subsequent Clinical and Biomarker Remission in Children with Crohn's Disease. Issue 7 (26th September 2020) - Rinawi, Firas; Ricciuto, Amanda; Church, Peter C; Frost, Karen; Crowley, Eileen; Walters, Thomas D; Griffiths, Anne M
Abstract: Background: Data on the association between early postinduction serum adalimumab (ADA) trough levels (TLs) and objective outcomes are scarce. The aim of this study was to investigate whether early ADA TLs at weeks 4 and 8 are associated with clinical and biomarker remission at week 24 in pediatric Crohn's disease (CD). Methods: Adalimumab TLs at weeks 4 and 8 were prospectively measured in anti-TNF-naïve children initiating treatment with ADA monotherapy for luminal inflammatory CD. The primary outcome was combined clinical and biomarker remission at week 24, defined as achieving steroid-free clinical remission (Pediatric CD activity index <10) and biomarker remission (fecal calprotectin <250 µg/g and CRP <5 µg/mL). Results: Among 65 patients, 39 (60%) achieved combined clinical/biomarker remission at week 24 without dose escalation. Adalimumab TLs at both weeks 4 and 8 were significantly higher in remitters vs nonremitters at week 24 ( P  < 0.001 and P  = 0.002, respectively). Adalimumab levels at weeks 4 and 8 were good predictors of combined clinical/biomarker remission at week 24 (area under the curve, 0.887, 95% CI, 0.798–0.942; and area under the curve, 0.761, 95% CI, 0.632–0.899, respectively). The best ADA TL cutoffs at weeks 4 and 8 for predicting clinical/biomarker remission at week 24 were 22.5 µg/mL (80% sensitivity, 90% specificity, positive likelihood ratio [LR+] 8.0, negative LR [LR-] 0.2) and 12.5 µg/mL (94% sensitivity, 60% specificity, LR+ 2.4, LR- 0.1), respectively. Higher induction doses per m 2 correlated positively with TLs at weeks 4 and 8. Conclusion: Greater early ADA exposure is associated with superior clinical/biomarker outcomes at week 24.